PENGARUH FAKTOR-FAKTOR KEPUASAN KERJA BAGIAN UMUM TERHADAP PRESTASI KERJA KARYAWAN RS DELTA SURYA DI SIDOARJO - SOFYAN LAZUARDI (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2014)
To support that employees working on a better performance, it is recommended to the company that the factors of job satisfaction every time continuously strived to be improved by giving motivation and evaluation of employee performance, improve working conditions and systems of remuneration and reward for employees achievement to boost the morale of other employees to join excel. From the research, it is known that the magnitude of the influence of the opportunity to advance on employee performance indicated by the value b1 = 0.1764 and significant because the t-test (= 1.99)> t-table (= 1.708). The amount of influence factors working conditions on employee performance is indicated by the value of b2 = 0.2240 and significant because of the t-test (= 3.097)> t-table (= 1.708). The magnitude of the effect of payroll on employee performance is indicated by the value of b3 = 0.5978 and significant because the t-test (= 5.336)> t-table (= 1.708), whereas the influence of factors supervision on employee performance is indicated by the value of b4 = 0, 3041 and significant because of the t-test (= 1.89)> t-table (= 1.708). Simultaneously, the influence of the factors of job satisfaction is indicated by the value of R2 = 70.30% and significant because the F-test (= 14.794)> F-table (= 2.76) on the right hand side of the test. Thus it can be said that the factors of job satisfaction factors include the opportunity to go forward, working conditions, salaries and supervision both partially and simultaneously have a significant effect on the performance of the employee. While most dominant factor influence on employee performance is a factor salary